Sistem Pendataan Peserta PKH Lolos Jalur Seleksi Perguruan Tinggi Berbasis Website Pada Lembaga Mitra Gerakan Ayo Kuliah Lampung - Edo Laksana Widodo; Rendy Lutfi Prabowo; Wartariyus Wartariyus; M. Iqbal Parabi (Jurnal Pepadun, 2023)
The Bakrie Center Foundation is a charitable organization established in 2010, dedicated to nurturing emerging leaders in Indonesia. Its vision is to identify and cultivate leaders across all strata of society throughout the Indonesian archipelago, with a mission to bolster their capabilities and foster a talent pool that will ultimately stimulate national development and economic growth. In the 6th edition of the Campus Leader Program, the Bakrie Center Foundation collaborated with partner institutions as part of the "Let's Go to Lampung" initiative. The Foundation recognized the effectiveness of the "Let's Go to Lampung" movement, which is geared towards providing education, motivation, and support to KPM PKH children. During the operational phase, there were challenges in data collection, prompting the founder of GAK Lampung to propose the development of a website for a Data Collection System designed to assist PKH children in navigating the university selection process, to be implemented at the partner institution of the "Let's Go to College" Movement (GAK) in Lampung.